Continuous generation of alginate microfibers with spindle-knots by using a simple microfluidic device. Issue 4 (8th December 2014) - Ji, Xiaobo; Guo, Song; Zeng, Changfeng; Wang, Chongqing; Zhang, Lixiong
Abstract : Calcium alginate microfibers with spindle-knots are fabricated by combining microfluidic technique with wet-spinning method. The structures of the knots can be conveniently regulated by changing the two-phase flow rate ratio and the micropipette diameter. Abstract : We developed a simple microfluidic-based method to fabricate calcium alginate microfibers with spindle-knots. A co-axial type microfluidic device installed with a micropipette at its outlet was used with a sodium alginate solution as the continuous phase and liquid paraffin as the dispersed phase. We examined the effect of the micropipette, its diameter, the dispersed phase to the continuous phase flow rate ratio and the physical properties of the oil used as the dispersed phase on the formation of the knots, the width and height of the knot, the interval between two adjacent knots, and the diameter of the fiber. Use of the micropipette is crucial to successful formation of the knots, as the oil phase microdroplets are deformed when flowing through it and retract after flowing out of it. The height and width of the knot increase and the interval decreases with increasing the flow rate ratio and the microdroplet diameter. The viscosity of the oil phase plays an important role in the successful formation of the knots. The alginate fibers with spindle-knots exhibit water collection capability. This method is expected to be used for the fabrication of other types of fibers with spindle-knots.